Is supervision training necessary? Reflecting on supervision as a student and novice supervisor - Arendse, D. (South African Journal of Higher Education, 2025)
The process of advancing through higher education involves the crucial role of supervision. It is, however, concerning that the training of postgraduate supervisors is often neglected. This article explored my personal experiences of supervision by comparing my past role as a postgraduate student with my present role as a postgraduate supervisor. This article emphasises the pressing need to better equip supervisors for the pivotal role they play in shaping students’ academic trajectory. This article draws attention to the indispensable value of engaging in supervision training and concurrently advocates for supervisors to participate in postgraduate supervision training. It is therefore prudent that we educate ourselves and embrace opportunities for learning that can better equip us for the role of supervision. We should also not assume that the attendance of supervisor courses would sufficiently educate us but we must rather embrace the practical exposure and experience that supervision offers us. This article therefore seeks to remind both novice and experienced supervisors that supervisor training is neccessary as it enriches us and assists us in unearthing our student's potential, which is the true essence of education.